Psychiatry Meets Cardiology: A Case Report on the Need for Mental Health Assessment in the Evaluation of Cardiovascular Symptoms - Asamoah, Kofi Tekyi; Dei-Asamoa, Richard (Case Reports in Psychiatry, 2022)
Cardiovascular symptoms like chest pain and palpitations are among the commonest reasons for outpatient hospital visits. Physician preoccupation with ruling out sinister cardiological diagnoses often results in a failure to recognise mental health-related disorders, which account for over 40% of such cases, especially among young women. These disorders can independently cause cardiovascular symptoms or worsen preexisting cardiovascular disease, worsening morbidity. The pathophysiology of mental stress-induced myocardial ischaemia involves increased levels of neurotransmitters, as opposed to anatomical obstruction seen in conventional coronary artery disease. This results in a battery of tests (including invasive assessments) which yield normal results, deepening the patient’s psychological stress. There is therefore an increased expenditure on healthcare with little assurance of wellness. Detection of these conditions is poorer in developing countries due to limited capacity in appreciating mental health disorders, though over 70% of mental health disorders occur in these countries. Two young ladies with no comorbidities who presented with chest pain and palpitations are reported in this paper. Laboratory investigations and specific cardiology-based tests were normal, but a thorough family and social history revealed underlying mental stresses, corroborated by a mental state examination. A diagnosis of panic disorder was made and once managed, symptoms abated and quality of life improved. We seek to emphasise that mental health disorders are an important cause of cardiovascular symptoms among young adults and must be actively sought by physicians to reduce the associated morbidity, as conventional tests for ischaemia are not useful in their diagnosis. Mental state examination should be done routinely in all clinical assessments to identify patients with subtle signs and improve their clinical outcomes. There must be commitment to build capacity among nonpsychiatrists to reduce the treatment gap.